PKM Pelatihan Penggunaan Aplikasi Komputer Di PT Javas Anugerah Perkasa Kota Bengkulu - Selviani, Diah; Lorita, Evi; Maryani, Desy; Sanjaya, Evantry (Jurnal Dehasen Untuk Negeri, 2024)
The Community Service Activity (PKM) was carried out by Lecturers and Students of Bengkulu Dehasen University in collaboration with the Bengkulu Province Apprenticeship Network Communication Forum (FKJP). The background of this activity is the still low ability of apprenticeship participants to use basic computer applications such as Microsoft Word, Excel, and PowerPoint, even though these skills are needed in the world of modern work. The purpose of this activity is to provide practical training on the use of computer applications to apprenticeship participants at PT. Javas Anugerah Perkasa in order to be able to improve their digital competencies. The activity was carried out through the method of lecture, demonstration, and direct practice in the computer laboratory. The training results showed an increase in the understanding and skills of participants in operating various office applications effectively. Participants also show high enthusiasm and realize the importance of mastery of information technology in supporting work productivity. This activity contributes positively to the capacity building of interns and supports government programs in developing human resources based on technology competencies.